Clinical researchDyslipidaemia in hypertensive obese type 2 diabetic patients in Jamaica - Gordon, Lorenzo; Ragoobirsingh, Dalip; Morrison, Errol; McGrowder, Donovan; Choo-Kang, Eric; Martorell, E. (Archives of Medical Science, 2010)
Introduction : Hypertension and obesity are common problems among diabetic patients accelerating progression of vascular diabetic complications. Material and methods : A two-stage stratified random sampling design was used, and individuals aged 15 years and over were interviewed. This cross-sectional study evaluated lipid abnormalities of 117 obese type 2 diabetic patients (28 males and 89 females), and 56 hypertensive obese type 2 diabetic patients (22 males and 34 females). Total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), very-low-density lipoprotein cholesterol (VLDL-C) and high-density lipoprotein cholesterol (HDL-C) concentrations were assayed using standard biochemical methods. Results : Hypertensive obese type 2 diabetic females had significantly higher mean serum concentrations of TC (p = 0.043), TG (p = 0.046), LDL-C (p = 0.040), TC/HDL-C ratio (p = 0.001) and LDL-C/HDL-C ratio (p = 0.003) compared with hypertensive obese non-diabetic females. Similar results were found in hypertensive obese type 2 diabetic males compared with hypertensive obese non-diabetic males. Hypertensive obese type 2 diabetic females had significantly higher serum TC, TG and TC/HDL-C ratio (p < 0.05) than hypertensive obese type 2 diabetic males. Hypertensive obese type 2 diabetic females had significantly higher mean serum concentrations of TG (p = 0.03) and TC (p = 0.01) than obese type 2 diabetic females. There was a significant association between blood glucose and LDL-C concentrations in type 2 diabetic subjects (r = 0.36; p < 0.05). Conclusion : Obese hypertensive type 2 diabetic females are exposed more profoundly to risk factors including atherogenic dyslipidaemia compared with males.